“The analysis of the importance of class size on effective teaching of English as foreign language with students at Segundo de bachillerato general unificado “A” at Unidad Educativa “San Vicente de Paùl” in the city of Riobamba, Chimborazo province in the academic term February -July 2016. - Chacha Soldado, Edwin Patricio (2017)
In order to improve the quality of teaching which has been the main purpose to raise school quality. Unfortunately, most of learning is not acquired as teachers expect. This research focuses on analyzing the effects of class size on effective teaching at 2nd year of Secondary Education at the “San Vicente de Paúl” Educative unit. The type of study is qualitative with exploratory level. This research was carried out with forty students who were classified into eighteen boys, twenty-two girls and one teacher. The qualitative method used was the ethnographic. An observation guide and an interview were applied in the academic period February-July 2016 which were developed bearing in mind the research objectives and the information regarding to the phenomenon. Some problems for an effective teaching are performed by class size as shown in this research. Teacher and students think that class size is an important determinant in the educational process. That is why; they have agreed that it acts on time for individual instruction, students’ engagements, class control, motivational strategies, and students’ attention, blocking the way to get an effective teaching and learning. In addition to the following research can help to understand the importance of the problem already mentioned in educational areas.